Transport Properties of Poly(lactic acid)/Clay Nanocomposites. Issue 12 (31st October 2019) - Kalendova, Alena; Smotek, Jiri; Stloukal, Petr; Kracalik, Milan; Slouf, Miroslav; Laske, Stephan
Abstract : Poly(lactic acid) (PLA) is one of the most promising sustainable alternatives to petroleum‐based polymers. One of the main applications is in the packaging industry. Therefore, this article deals with the evaluation of gas transport properties polylactic acid 2003D nanocomposite. Montmorillonite‐based fillers, Cloisite® 10A, 20A, 30B and natural Cloisite® Na +, intended to enhance the transport properties, were incorporated into a series of PLA films. The influence of the additive on the transport properties was studied under the conditions of melt processing. Further material morphology was assessed using X‐ray diffraction and transmission electron microscopy. The best results achieved compositions with PLA/Cloisite10A and Cloisite 30B with improvement more than 50%. POLYM. ENG. SCI., 59:2498–2501, 2019. © 2019 Society of Plastics Engineers